The Implementation of Process Based Approach in Teaching Writing on The Tenth Grade Students in Senior High School - Made Hendrawan Pangestu; P. A. K. Juniarta; G. Mahendrayana (Indonesian Journal Of Educational Research and Review, 2022)
In the learning process, language is one of the most important communication tools for humans in conveying messages, feelings, and ideas from every human being (Dutta, 2020). Language also helps a person to form a word, clause, and sentence as the main communication tool. In addition, language can also be divided into four parts which are the basic skills of language, especially English, namely listening, speaking, reading, and writing. This study aims to analyze the implementation of the Process-Based Approach and the problems of it faced by English teachers in teaching writing to tenth grade students. The method used is descriptive research method using observation and interview techniques. The result of this study is that an English teacher uses a five-step process-based approach in teaching writing namely: pre-writing, compiling, revising, editing, and publishing. Then, there are three indicators, namely: lack of a process-based approach, teaching ability, and teaching habits. First, is the implementation of the revision and editing stages are still lacking. Second, time constraints make most students experience obstacles. Third, the teacher's habits can affect the character and abilities of students. That is the result of the research that there are still many techniques and ways to apply the five stages and also there are still some obstacles in the application of the approach.